Hemocompatibility studies in nanotoxicology: Hemolysis or eryptosis? (A review) - Tkachenko, Anton (Toxicology in vitro, 2024)
Hemocompatibility evaluation is an important step in nanotoxicological studies. It is generally accepted that nanomaterials promote lysis of erythrocytes, blood clotting, alter phagocytosis, and upregulate pro-inflammatory cytokines. However, there are no standardized guidelines for testing nanomaterials hemocompatibility despite the fact that nanomaterials enter the bloodstream and interact with blood cells. In this review, the current knowledge on the ability of nanomaterials to induce distinct cell death modalities of erythrocytes is highlighted primarily focusing on hemolysis and eryptosis. This review aims to summarize the molecular mechanisms underlying erythrotoxicity of nanomaterials and critically compare the sensitivity and efficiency of hemolysis or eryptosis assays for nanomaterials blood compatibility testing. The list of eryptosis-inducing nanomaterials is growing, but it is still difficult to generalize how physico-chemical properties of nanoparticles affect eryptosis degree and molecular mechanisms involved. Thus, another aim of this review is to raise the awareness of eryptosis as a nanotoxicological tool to encourage the corresponding studies. It is worthwhile to consider adding eryptosis to in vitro nanomaterials hemocompatibility testing protocols and guidelines.
Keywords: testování materiálů; Hemolysis; nanostruktury; erytrocyty; hemolýza; Animals; lidé; Materials Testing; Nanostructures; zvířata; Erythrocytes; Eryptosis; eryptóza; Humans